Deaf in the USSR : Marginality, Community, and Soviet Identity, 1917-1991 - Shaw, Claire L. (Book collections on Project MUSE., 2017)
Claire L. Shaw asks what it meant to be deaf in a culture that was founded on a radically utopian, socialist view of human perfectibility. Shaw reveals how fundamental contradictions inherent in the Soviet revolutionary project were negotiated?both individually and collectively - by a vibrant and independent community of deaf people who engaged in complex ways with Soviet ideology. Deaf in the USSR engages with a wide range of sources from both deaf and hearing perspectives - archival sources, films and literature, personal memoirs, and journalism?to build a multilayered history of deafness. This book will appeal to scholars of Soviet history and disability studies as well as those in the international deaf community who are interested in their collective heritage. Deaf in the USSR will also enjoy a broad readership among those who are interested in deafness and disability as a key to more inclusive understandings of being human and of language, society, politics, and power.